2021
DOI: 10.3390/sports9070095
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the COVID-19 Environments on Changes in Body Composition in Japanese Elite Fencing Athlete

Abstract: The Japanese government declared a state of emergency from 7 April to 25 May to limit people’s movement due to the coronavirus disease (COVID-19) pandemic. This pandemic negatively affects athletes’ body composition due to inactivity. Therefore, we compared the body composition data (i.e., fat-free mass (FFM) and fat mass (FM)), of 43 Japanese elite fencers (22 men, 21 women), in September 2019 for baseline, and of 21 (12 men, 9 women) who completed the following measurements in June 2020 (POST; immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 14 publications
1
23
4
1
Order By: Relevance
“…Results of our study are somewhat different to what has been reported in the general population in response to the COVID-19 lockdown, which have found weight gain that was partially due to a decrease in activity [15,16]. Prior studies in athletes and nonathlete college students reported a gain in body fat and loss of muscle mass during COVID-19, despite a shorter window of assessment compared to our study (2 months vs. 6-7 months) [5,17,18]. The study of elite fencing athletes by Yasuda, et al [5] showed no change in body composition for men but a gain in fat mass for women.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Results of our study are somewhat different to what has been reported in the general population in response to the COVID-19 lockdown, which have found weight gain that was partially due to a decrease in activity [15,16]. Prior studies in athletes and nonathlete college students reported a gain in body fat and loss of muscle mass during COVID-19, despite a shorter window of assessment compared to our study (2 months vs. 6-7 months) [5,17,18]. The study of elite fencing athletes by Yasuda, et al [5] showed no change in body composition for men but a gain in fat mass for women.…”
Section: Discussioncontrasting
confidence: 99%
“…Diet and PA quality responses of 1 (A lot worse) and 2 (Slightly worse) and 4 (Slightly better) and 5 (A lot better) were combined into single categories COVID-19 lockdowns on athlete body composition show conflicting results. Two studies, one in football players [4] with 4 months between pre-and post-COVID-19 measurements and a 2-month study in fencing athletes [5], both showed a gain of fat mass and loss of muscle mass. Alternatively, a study in soccer athletes showed no change in body composition [6] during 1 month in lockdown.…”
Section: Self-reported Changes In Diet and Pa Behaviors Questionsmentioning
confidence: 99%
“…The insufficient training stimulus, the reduction in the amount of physical activity in combination with social distancing and home isolation resulting from the Covid-19 quarantine promotes sedentary behavior and impaired nutritional habits [ 9 , 17 , 36 ]. Therefore, these could lead to a positive energy balance and negatively affect athletes’ body mass and body composition [ 17 , 22 , 37 , 38 ]. Previous investigations reported significant increases in body mass, body fat, and a decrease in resting metabolic rate following ~ 42 days of training cessation in athletes [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these could lead to a positive energy balance and negatively affect athletes’ body mass and body composition [ 17 , 22 , 37 , 38 ]. Previous investigations reported significant increases in body mass, body fat, and a decrease in resting metabolic rate following ~ 42 days of training cessation in athletes [ 38 , 39 ]. In this study, no significant differences were found in body weight, body mass index, and body fat percentage, whereas lean body mass was significantly increased following the home-based training program during Covid-19 restriction in high-level kayak athletes (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Athletic department staff should be aware of how breaks from campus impact athletes and have protocols in place to best help athletes during these times. lockdowns in the spring of 2020 [20,21]. These changes could be due to restrictions placed on gyms and other activities in parts of the country during the winter of 2020/21.…”
Section: Discussionmentioning
confidence: 99%